Identification and Immobilization of an Invertase With High Specific Activity and Sucrose Tolerance Ability of Gongronella sp. w5 for High Fructose Syrup Preparation - Zhou, Gang; Peng, Can; Liu, Xiaosa; Chang, Fei; Xiao, Yazhong; Liu, Juanjuan; Fang, Zemin (Frontiers in Microbiology, 2020)
Invertases catalyze the hydrolysis of sucrose into fructose and glucose and can be employed as an alternative in producing high fructose syrup. In this study, we reported the heterologous expression of an invertase gene (GspInv) of Gongronella sp. w5 in Komagataella pastoris. GspInv activity reached 147.6±0.4 U/mL after five days of methanol induction. GspInv is invertase with high specific activity showing a specific activity of 2,776.1±124.2 U/mg toward sucrose. GspInv showed high tolerance to sucrose (IC50=1.2 M), glucose (IC50>2 M), fructose (IC50=1.5 M), and a variety of metal ions that make it an ideal candidate for high fructose syrup production. A carbohydrate-binding module was sequence-optimized and fused to the N-terminus of GspInv. The fusion protein had the highest immobilization efficiency at room temperature within 1 h adsorption, with 1 g of cellulose absorption up to 8,000 U protein. The cellulose-immobilized fusion protein retained the unique properties of GspInv. When applied in high fructose syrup preparation by using 1 M sucrose as the substrate, the sucrose conversion efficiency of the fused protein remained at approximately 95% after 50 h of continuous hydrolysis on a packed bed reactor. The fused protein can also hydrolyze completely the sucrose in sugarcane molasses. Our results suggest that GspInv is an unusual invertase and a promising candidate for high fructose syrup preparation..